Implementasi Peraturan Pemerintah Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Nomor 39 Tahun 2012 Tentang Pedoman Pengembangan Budaya Kerja di Pemerintah Provinsi Bali - Rachmat Fauzi, Arief (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The policy regarding work culture has existed since 2002, but in 2012 the government made changes. In 2020 the score/value of implementing work culture in government agencies ranges from 45%-66%. This shows that work culture has not been seen as an important thing. However, the Bali Provincial Government sees that work culture is an important aspect, this is indicated by the commitment of the Bali Provincial Government to those stipulated by the Governor's Regulation on ASN Work Culture. Departing from this, this study aims to answer the application of work culture in the Bali Provincial Government. This study aims to determine the application of work culture in the Bali Provincial Government so far and to find out the problems in its application. This study uses a qualitative descriptive method, with data collection techniques by means of interviews or interviews with stakeholders, and uses the results of documentation by reviewing the results of events that have passed, as well as online data searches. In implementing work culture policies, researchers refer to Rondinelli and Cheemayang who explain about the four variables that affect the performance and impact of a policy. This study recommends that it is necessary to evaluate PermenPAN 01/2007 concerning Guidelines for Evaluation of the Implementation of Work Culture Development in Government Agencies, because the measuring tools contained in the policy are considered not to be accurate to see the impact of work culture policies. In addition, it is necessary to pay attention again to the monev instrument, so that when government agencies carry out monev work culture is able to assist in improving the implementation of work culture in the future.